"To Promote That Demand": Toward a History of the Marketing White Paper as a Genre. (January 2018) - Malone, Edward A.; Wright, David
Although various types of documents are called white papers, in technical marketing communication the white paper is usually a document that describes a new or improved technology in order to generate interest in—and promote sales of—that technology. Most sources discussing the history of the white paper assume that marketing white papers evolved from government white papers. They conflate genre history with etymology. At some point in the mid-20th century, the term white paper —denoting a type of government policy document—began being applied to other types of documents, including eventually a particular form of technical marketing communication. This article proposes a revised history of the marketing white paper as a genre. By examining the formal features and characteristic substance of white papers through the lens of their pragmatic value as social action, we show that the marketing white paper of today has much in common with documents from the 16th, 17th, and 18th centuries.